2016
DOI: 10.1002/adfm.201602645
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature BiScO3‐PbTiO3 Piezoelectric Vibration Energy Harvester

Abstract: Conventionally, effective mechanical vibration energy harvesting is based on (Pb,Zr)TiO3 (PZT) ceramics, poly(vinylidene fluoride) (PVDF) polymers or PVDF/PZT or other piezoelectric composite materials, and their working temperature is normally limited to room temperature (R‐T) or below 150 °C. Here, bismuth scandium lead titanate (BiScO3‐PbTiO3, abbreviated as BSPT) ceramic is reported which has a high Curie temperature point around 450 °C and its application for high‐temperature (H‐T) vibration energy harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 38 publications
1
52
1
Order By: Relevance
“…The temperature coefficient of V out , η V , can be maintained below ±20% between 100 and 250°C (as shown in the inset of Figure D). Recently, Dong et al reported cantilever and barbell‐shaped high‐temperature piezoelectric vibration energy harvester. The stable output voltage is obtained in the temperature range of 100‐200°C and 150‐250°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature coefficient of V out , η V , can be maintained below ±20% between 100 and 250°C (as shown in the inset of Figure D). Recently, Dong et al reported cantilever and barbell‐shaped high‐temperature piezoelectric vibration energy harvester. The stable output voltage is obtained in the temperature range of 100‐200°C and 150‐250°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid development of ultralow power consumption electronics such as wireless sensor network and portable electronic devices, more and more attention has been paid to new energy sustainable solutions that replace traditional batteries . Energy harvesting technology may be considered an ultimate solution to replace batteries and provide a long‐term power supply for wireless sensor networks, which draws much attention recently all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…17,23 In addition, PE performance and lifetime are compromised in high-temperature environments. 26 Flexible PE materials struggle to exceed average efficiency as well as higher fabrication cost and complexity. 23,24 Synchronous switch harvesting inductor circuits are frequently adapted in research and development (R&D), because they reduce the internal capacitive impedance effect and accommodate fluctuations in vibration frequency and amplitude.…”
Section: Piezoelectric Ehmentioning
confidence: 99%
“…The drop in potential causes electrons to flow between the electrodes attached to each surface and connected with a circuit. 17 An ES design 26 with less material and lower cost uses 2 dissimilar polymer sheets without an interlayer-binding sandwiched structure. Nevertheless, it generates a relatively small energy density, and external voltage sources are required for EH operation.…”
Section: Electrostatic Ehmentioning
confidence: 99%
“…PZT-MEMS harvester showed lower thermal degradation rate than PZT-bulk harvester in the temperature range from 25 to 100°C. Furthermore, Jingen Wu et al 23) have reported that electric power-output property of BiScO 3 PbTiO 3 (BSPT) bimorph-PVEHs which have a high curie temperature (T C ³450°C). A voltage of the BSPT bimorph-PVEHs initially increased in the temperature range from 25 to 150°C, however, the voltage decreased dramatically above 150°C.…”
Section: )10)mentioning
confidence: 99%